2018
DOI: 10.1037/pag0000261
|View full text |Cite
|
Sign up to set email alerts
|

Individual differences in loss aversion and preferences for skewed risks across adulthood.

Abstract: In a previous study, we found adult age differences in the tendency to accept more positively-skewed gambles (with a small chance of a large win) than other equivalent risks, or an age-related positive-skew bias. In the present study, we examined whether loss aversion explained this bias. 508 healthy participants (ages 21–82) completed measures of loss aversion and skew preference. Age was not related to loss aversion. While loss aversion was a significant predictor of gamble acceptance, it did not influence t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 24 publications
0
17
4
Order By: Relevance
“…One surprising result that was that we did not see any age di erences in acceptance of skewed gambles. This is surprising because it was in direct contrast to prior studies that have found a relationships (Seaman et al, 2018(Seaman et al, , 2017. Even limiting our sample to those who answered a similar question (Study 1, expected value = $0, N = 41), we see no e ects of age (although it should be noted this subsample skews older than the whole study sample;…”
Section: Discussioncontrasting
confidence: 66%
See 1 more Smart Citation
“…One surprising result that was that we did not see any age di erences in acceptance of skewed gambles. This is surprising because it was in direct contrast to prior studies that have found a relationships (Seaman et al, 2018(Seaman et al, , 2017. Even limiting our sample to those who answered a similar question (Study 1, expected value = $0, N = 41), we see no e ects of age (although it should be noted this subsample skews older than the whole study sample;…”
Section: Discussioncontrasting
confidence: 66%
“…We predict that the positive-skew bias will increase with greater skewness in both certain (Study 1) and uncertain (Study 2) conditions. Further, we wanted to examine how the age-related positive-skew bias observed in our previous studies (Seaman et al, 2018(Seaman et al, , 2017 is impacted by these di erent levels of skewness. We predict that the positive-skew bias will increase with age and that this bias will become more pronounced with higher degrees of skewness.…”
mentioning
confidence: 97%
“…These accounts might suggest that older individuals would be less loss averse because emotion regulation improves with age (Gross et al, 1997). Previous research on age and loss aversion has yielded mixed results (Mikels & Reed, 2009;Pachur, Mata, & Hertwig, 2017;Seaman, Green, Shu, & Samanez-Larkin, 2018;Weller, Levin, & Denburg, 2011). Across the five samples, we examined whether age is associated with loss aversion.…”
Section: Preference Construction Shapes Loss Aversionmentioning
confidence: 96%
“…Thinking about decumulation decisions in a loss aversion context suggests applying loss aversion manipulations to interventions. Various methods can measure loss aversion at the individual level (e.g., Abdellaoui, Bleichrodt, & Paraschiv, 2007; Brooks & Zank, 2005; Payne, Shu, Webb, & Sagara, 2015; Seaman, Green, Shu, & Samanez-Larkin, 2018; Toubia, Johnson, Evgeniou, & Delquié, 2013). As with the temporal discounting measures noted above, knowledge of a given individual’s loss aversion level may assist policy makers in customizing interventions to better assist people’s decumulation decision making.…”
Section: Key Psychological Inputs To Decumulation Decisionsmentioning
confidence: 99%